Genetic variability, heritability, correlation and path analysis for yield and quality traits in rice (Oryza sativaL.) - C. CHERALU, K. RUKMINI DEVI, K. PARIMALA, V. VENKANNA and (The Journal of Research, PJTSAU, 2017)
In the present study 29 rice genotypes were evaluated for yield, its components and also grain quality characters at Regional Agricultural Research Station, Warangal during 2010. The estimates of phenotypic coefficients of variation (PCV) were slightly higher than those of genotypic coefficients of variation (GCV).Grain yield per plant, grains per panicle, test weight, water uptake, effective tillers, volume expansion ratio and kernel width recorded high (> 20%) GCV and PCV. High heritability coupled with high genetic advance as percent of mean was observed for yield per plant, grains per panicle, water uptake, effective tillers per hill, head rice recovery, test weight, volume expansion ratio, kernel width and plant height. The correlation studies indicated that plant height, effective tillers, panicle length, grains per panicle and test weight were positively and non significantly associated with seed yield and similarly for plant height with panicle length and grains per panicle ; effective tillers with test weight. Grains per panicle had negative significant association with test weight. Hulling percent, milling percent and alkali spreading value were positively correlated with head rice recovery. Path analysis revealed that plant height, grains per panicle, effective tillers, test weight and panicle length had highest positivedirect effect on seed yield. It indicated that these characters were contributed more towards seed yield per plant.Hulling (%), milling (%)and alkali spreading value had positive effect on head rice recovery.